Preheparin serum lipoprotein lipase mass interacts with gender, gene polymorphism and, positively, with smoking - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2009)
Background: Correlates of preheparin serum lipoprotein lipase (LPL) mass and its associations with the likelihood of metabolic syndrome (MS) and coronary heart disease (CHD) were investigated. Methods: A cross-sectional study was carried out in a population sample (n=352, median age 55). MS was defined according to modified Adult Treatment Panel III criteria. Results: Age-adjusted geometric mean preheparin LPL concentrations were 58.6 +/- 1.04 ng/mL in men and 66.9 +/- 1.03 ng/mL in women (p < 0.004). A positive interaction with both the LPL X447 allele (p < 0.034) and age-adjusted smoking status (p=0.026 in men and p=0.11 women) was observed. LPL mass was significantly correlated in both genders with high-density lipoprotein (HDL)-cholesterol and inversely with triacylglycerol levels and HOMA index. In multiple linear regression analysis, LPL mass was significantly associated with genotype, gender, age, adiponectin, smoking status and HDL-cholesterol, and in women with C-reactive protein after adjustment for body mass index, triacylglycerol and insulin. Significantly low sex- and age-adjusted serum LPL mass was observed in cases of MS, hypertension and CHD. Logistic regression analysis after adjustment for age, sex, adiponectin and S447X polymorphism demonstrated that LPL mass was inversely associated with CHD in men and both genders (p=0.02), with hypertension confined to women (p=0.04) and with MS likelihood in both genders combined and women [odds ratio 1.51 (95% Cl 1.14-2.00) for halving the likelihood]. Conclusions: LPL X447 genotype, female gender and smoking habit interact in increasing preheparin serum LPL mass in Turkish adults. Serum LPL mass is inversely associated with MS and CHD, independent of confounders, and probably reflects insulin sensitivity.
Keywords: atherogenic dyslipidemia; gender interaction; lipoprotein lipase gene; metabolic syndrome; smoking habit; METABOLIC SYNDROME; POSTHEPARIN PLASMA; RISK; MEN; DEFINITION; DISEASE; PROTEIN; LIPIDS; WOMEN; AGE